HUBUNGAN PERSEPSI TENTANG KESEHATAN REPRODUKSI DENGAN PERNIKAHAN DINI PADA REMAJA DI DESA BUNDER KECAMATAN PADEMAWU PAMEKASAN TAHUN 2016 - sylvina rahmawati; Adivtian Ragayasa (JURNAL PENELITIAN KESEHATAN, 2017)
Early marriage is a marriage conducted under age 20 for women and age 25 for men, based on the results of preliminary studies were conducted in villages bunder of 10 respondents were given a questionnaire that perform early marriage by 7 respondents say do not know about the reproductive health of the restriction A healthy marriage age. The purpose of this study to determine the relationship of perception of reproductive health in adolescents with early marriage.The research method uses analytic survey with cross sectinal. The population is nwanita Adolescents aged 20-30 years who were married as many as 36 respondents and the sample 33 respondents using simple random sampling technique. Data were analyzed using analysis univariable and bivariable using chi square test.The results showed respondents' negative perception about reproductive health and early marriages as much as 75%. Based on statistical test of chi squre got value ρ value = 0.013 α = 0.05 this study it can be concluded that Ho refused Ha accepted meaning there is a perception of reproductive health in adolescents with early marriage.Health workers, especially midwives are expected to assist and provide IEC and counseling to young families and the community about early marriage so that society and Understanding Your teens about healthy age limit for a wedding.                                               Keywords: Perception, Early Marriage